Liquidity Constraints and Imperfect Information in Subprime Lending - Adams, William; Einav, Liran; Levin, Jonathan (American Economic Review, 2009)
We present new evidence on consumer liquidity constraints and the credit market conditions that might give rise to them. We analyze unique data from a large auto sales company serving the subprime market. Short-term liquidity appears to be a key driver of consumer behavior. Demand increases sharply during tax rebate season and purchases are highly sensitive to down-payment requirements. Lenders also face substantial informational problems. Default rates rise significantly with loan size, providing a rationale for loan caps, and higher-risk borrowers demand larger loans. This adverse selection is mitigated, however, by risk-based pricing. (JEL D14, D82, D83, G21)